Simulation-Based Neonatal Resuscitation Education for Undergraduate Anesthesia Students: A Pre- and Post-Evaluation of Knowledge and Clinical Skills - Debas Yaregal Melesse; Henos Enyew Ashagrie (Anesthesiology Research and Practice)
Background. Nearly one in five hundred babies unexpectedly need resuscitation at birth, and the need for resuscitation is often unpredictable. A large majority of these deaths occur in low-resource settings and are preventable. Appropriate resuscitation techniques are crucial to the survival of newborn infants. Therefore, producing skilled health professionals in teaching institutions is mandatory to perform this activity. Objective. The study aimed a pre- and post-evaluation of knowledge and clinical skills performance of anesthesia students completing simulation-based neonatal resuscitation training at a Teaching Referral Hospital. Methods. A pre-post-intervention study was conducted on undergraduate final-year anesthesia students at Comprehensive and Specialized Teaching Referral Hospital, Ethiopia. We used a validated checklist to follow the students’ performance (American Heart Association, 2005, and Ogunlesi et al., 2012). The data were collected through this checklist. The collected data were analyzed with statistical package for social sciences (SPSS) version 20. Categorical variables were analyzed with chi-square test, and a p-value <0.05 was considered as statistically significant. Results. A total of 51 students participated in the study. Twenty of them were females. The pre-intervention knowledge of the respondents about aspects of evaluation for neonatal resuscitation was 90.2%, and post-intervention was 94.1%; the knowledge of the respondents about aspects of appropriate actions at pre- and post-interventions was 73.4% and 83.1%, respectively. Conclusions and recommendations: This study showed that there was improvement of post-interventions knowledge and clinical skills of undergraduate anesthesia students for both aspects of evaluation and appropriate actions for neonatal resuscitation. We recommend that students who attached clinical anesthesia practice should take at least simulation-based training at skill laboratories timely.